Spatially heterogeneous structure-function coupling in haemodynamic and electromagnetic brain networks - Liu, Zhen-Qi; Shafiei, Golia; Baillet, Sylvain; Misic, Bratislav (NeuroImage (Orlando, Fla.), 2023)
•We comprehensively study structure-function coupling between dMRI-derived structural connectivity and MEG/fMRI-derived functional connectivity.•We show consistently spatially heterogeneous structure-function coupling across modalities.•We find stronger coupling in slower and intermediate frequency bands.•Network communication models capture different coupling patterns in different bands.•Structure-function coupling reflects the sensorimotor-association axis and laminar differentiation. The relationship between structural and functional connectivity in the brain is a key question in connectomics. Here we quantify patterns of structure-function coupling across the neocortex, by comparing structural connectivity estimated using diffusion MRI with functional connectivity estimated using both neurophysiological (MEG-based) and haemodynamic (fMRI-based) recordings. We find that structure-function coupling is heterogeneous across brain regions and frequency bands. The link between structural and functional connectivity is generally stronger in multiple MEG frequency bands compared to resting state fMRI. Structure-function coupling is greater in slower and intermediate frequency bands compared to faster frequency bands. We also find that structure-function coupling systematically follows the archetypal sensorimotor-association hierarchy, as well as patterns of laminar differentiation, peaking in granular layer IV. Finally, structure-function coupling is better explained using structure-informed inter-regional communication metrics than using structural connectivity alone. Collectively, these results place neurophysiological and haemodynamic structure-function relationships in a common frame of reference and provide a starting point for a multi-modal understanding of structure-function coupling in the brain.